Pemberdayaan Ibu-Ibu PKK Melalui Seminar Risalatul Haid di Desa Payaman, Solokuro, Lamongan - Ahmad Zakariya Al Anshori; Isyna Finnurika; Ahmad Masykur Amin; Aisy Wildatil Aimmah (Santri : Journal of Student Engagement, 2026)
This community service program aims to empower women members of PKK by enhancing their understanding of fiqh al-haid based on the book Risalatul Haid in Gayam Hamlet, Payaman Village, Solokuro District, Lamongan Regency. This activity was motivated by the limited understanding among women regarding basic rulings on menstruation, which directly affects the validity of worship practices and family religious education, particularly in the post-pandemic period. The program employed a Participatory Action Research (PAR) approach through the stages of to know, to understand, to plan, to action, and to reflection. The activities were conducted in the form of educational seminars, interactive lectures, and question-and-answer sessions involving PKK women as the main participants. The results indicated a high level of participant engagement and a significant improvement in understanding the distinctions between menstruation, postpartum bleeding, and abnormal bleeding, along with their religious implications. Furthermore, the program fostered greater awareness of women’s strategic role as primary educators within the family. Therefore, the Risalatul Haid seminar proved to be an effective educational medium for strengthening religious literacy and community-based women empowerment.